A Study of Mobile User Movements Prediction Methods - J. Venkata Subramanian; S. Govindarajan (Institute of Advanced Engineering and Science, 2018)
For a decade and more, the Number of smart phone users count increasing day by day. With the drastic improvements in Communication technologies, the prediction of future movements of mobile users needs also have important role. Various sectors can gain from this prediction. Communication management, City Development planning, and locationbased services are some of the fields that can be made more valuable with movement prediction. In this paper, we propose a study of several Location Prediction Techniques in the following areas